Pelaksanaan Pasal 280 Undang-Undang Republik Indonesia Nomor 7 Tahun 2017 tentang Pemilihan Umum: Pelanggaran Kampanye Pemilu 2019 di Kabupaten Blitar - Abdul Hakam Sholahuddin; Anik Iftitah; Uun Dewi Mahmudah (Universitas Islam Balitar, Blitar, 2019)
Potential for Election violations is prone to occur in the campaign stage as a moment for the Election Contestants in the 2019 Election to introduce themselves to the public to be elected. Considering this, the empirical legal research